Multi-physics modeling of a symmetric flat-tube solid oxide fuel cell with internal methane steam reforming. (29th October 2022) - Li, Yuqing; Wang, Linjing; Gu, Yuchen; Xing, Bowen; Chu, Zhenhua; Huo, Haibo; Yang, Jun; Wang, Yang; Xu, Jingxiang
Abstract: Methane is regarded as one of the ideal fuels for solid oxide fuel cells (SOFCs) due to its huge reserves and transportation properties. In this study, a 3D numerical model coupling with chemical reaction, electrochemical reaction, mass transfer, charge transfer, and heat transfer is developed to understand the heat and mass transfer processes of methane steam direct internal reforming based on double-sided cathodes (DSC) SOFC. After the model verification, the parametric simulations are performed to study the effects of operating voltage, inlet temperature, and steam to carbon (S/C) ratio on the performance of a DSC. It is found that the non-uniform distribution of flow rate among channels results in the non-uniform distribution of each physical field. Increasing the inlet temperature significantly enhances the performance of DSC, however, when the temperature is above 1073 K, the concentration loss and the temperature gradient of DSC increase, which is not conducive to the long-term operation of the DSC. In addition, we revealed the effect of the S/C ratios on the heat and mass transfer process. This study provides an insight into the heat and mass transfer process of SOFC with a mixture of steam and methane and operating conditions for enhancing the performance. Highlights: A 3D multi-physics coupled model of methane-fueled SOFC was established. The channel structure substantially influences the physical field distribution. Increasing inlet temperature will increase the temperature gradient of anode. S/C ratios remarkably affect the current density and chemical reaction rate.